Production Performance of Brahman Cross Steer Feed with Concentrate Containing Kapok Seed Meal - Soeprapto, H (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
The research was conducted to investigate the weight gain and meat physical quality of Brahman cross steer (BX) fed with concentrate containing kapok seed meal (Ceiba pentandra). The research used 12 heads of two years age Brahman cross steer with body weight of 324 Â± 11.29 kg. the steer were kept in individual barn and offered with concentrate containing three level of kapok seed meal. i.e: R1 (10%), R2 (20%) and R3 (30%). A completely randomized design with four replications was employed. Elephant grass (pennisetum purpureum) was fed along with concentrate in 20 : 80% ratio. A total amount of feed given to the cattle was 2.5 % of the body weight on the basis of dry matter and offered twice a day in the morning and the afternoon. Water was given ad libitum. Result showed that there was no significant different on daily gain and meat physical quality. Daily gain of R1, R2 and R3 was 0.73 kg, 0.84 kg, and 0.75 kg of respectively. There was significant different in carcass percentage i.e. 52.57, 50.84, and 48.58 for R1, R2 and R3 respectively. Physical quality of meat consisting of colour, pH, water holding capacity (WHC), cooking loss (CL) and tenderness indicated non significant effect. The pH value of observed muscle in Longisinus dorsi (LD), semitendinosus (ST), and bicep femoris (BF), was 5.80 (R1) 5.87(R2) and 5.81 (R3), meat colour score was 5.48 (R1), 5.58 (R2) and 5.59 (R3), water holding capacity % was 36.40 (R1), 39.66 (R2) and 34,09 (R3), and cooking loss (5) was 46.62, 44.17 and 46.19 for R1, R2 and R3 respectively. Result of meat tenderness (g/mm/second) was 57.84 (R1), 56.05 (R2) and 59.41 (R3). In relation to price, feed consumption, and daily gain indicated that feed cost per gain was Rp. 2.991.50 (R1), Rp. 2.638.50 (R2), Rp. 2.965.25 (R3), and income over feed cost was Rp. 818.25 (R1), Rp. 1.238.95 (R2), and Rp. 855.80 (R3) respectively. The result showed that the use of 20% of Kapok Seed meal in concentrate (R2), although there was no significant effect, gives the most efficient result. (Animal Production 7(3): 189-193 (2005)Â Key Words : Brahman Cross Steer, Body Weight, Meat Quality, Kapok Seed Meal.